2008
DOI: 10.1007/s00417-008-0871-y
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidant–antioxidant balance, peroxide and catalase activity in the aqueous humour and serum of patients with exfoliation syndrome or exfoliative glaucoma

Abstract: These findings suggest that in XFS oxidative stress is counterbalanced in the aqueous, whereas the development of XFG is accompanied by a disruption of this balance in favour of oxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 36 publications
2
31
2
1
Order By: Relevance
“…17 The difference between the study of Koliakos et al and ours might be due to the differences in life style, dietary habits and genetic background of the subjects in the two studies. 17 Hence, in another Turkish study, Yılmaz et al reported nonsignificantly lower catalase activities in PEX patients compared to controls, similar to our study. 5 In addition to these studies on PEX, catalase activity was also measured in other disorders of the eye.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…17 The difference between the study of Koliakos et al and ours might be due to the differences in life style, dietary habits and genetic background of the subjects in the two studies. 17 Hence, in another Turkish study, Yılmaz et al reported nonsignificantly lower catalase activities in PEX patients compared to controls, similar to our study. 5 In addition to these studies on PEX, catalase activity was also measured in other disorders of the eye.…”
Section: Discussioncontrasting
confidence: 47%
“…Koliakos et al found that catalase activity in the aqueous humor from PEX (10.1±4.5 U/ml) and PEG (12.2±6 U/ml) patients was significantly lower than that measured in the normal aqueous humor (14.6±1.9 U/ml). 17 Similarly, a significantly lower serum catalase activity was found in PEX (103±21.4 U/ml) and PEG (116±38 U/ml) patients compared to the controls (189.6±84.3 U/ml). 17 The difference between the study of Koliakos et al and ours might be due to the differences in life style, dietary habits and genetic background of the subjects in the two studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, we aimed to explore this phenomenon by comparing parameters related to oxidative balance in NTG and PEXG. The oxidant/antioxidant parameters in PEX and PEXG patients has been studied extensively and OS markers were found to have risen, while antioxidants have diminished, resulting in an oxidative balance in favor of oxidants [9][10][11][12][13]. There are fewer studies on NTG, but an increase in OS has been associated with it nonetheless [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoexfoliation glaucoma (PEXG) is also associated with OS, in which abnormal extracellular fibrillar material is accumulated in the eye, obstructing humor drainage [8]. PEX syndrome (PEX) is, in fact, an age-related systemic disorder of the extracellular matrix, also observed in the vascular system and various organs [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%